Webster's New World Roget's A-Z thesaurus - Charlton Laird (Wiley Publishing, 1999)
This new edition of the renowned Webster's New World Thesaurus combines a thematic index-based on Roget's original categories with the proven usefulness of its A-Z listing. New introductory material and an interpretive essay on Roget and his work reintroduce Roget's organizational technique to a new generation of thesaurus users.